Implementation of best medical therapy for cardiovascular risk factors in vascular surgery patients treated in a tertiary referral regional unit. Issue 9 (25th March 2014) - McGrogan, D.; Mark, D.; Lee, B.; O'Donnell, M. E.
Summary Objective Current clinical evidence reports that antiplatelet, statin, angiotensin‐converting enzyme inhibitor and beta blockade therapies have advantageous effects on vascular surgery patient morbidity and mortality. Unfortunately, such patients appear to be less likely to receive optimal medical management when compared with coronary artery disease patients. This study assessed medical therapy prescribing in patients attending a regional vascular surgery unit. Methods A retrospective review between February 2010 and February 2011 was performed for patients undergoing aortic aneurysm, carotid, peripheral arterial and amputation surgeries. Gender, age, smoking history, body mass index and cardiovascular risk factors were documented from inpatient charts. Current admission medications and subsequent modification by the vascular team were recorded. Results Two hundred and forty‐four patients (male = 165, mean age = 71 years) were identified. Prevalence of hypertension, hypercholesterolaemia, myocardial infarction, angina, stroke and diabetes was higher than in the general population. A total of 201 (82.3%) patients were on antiplatelets or antithrombotics upon admission to the vascular ward, which was improved to 231 (94.6%) patients on discharge. A total of 180 (73.7%) patients were on lipid‐lowering therapy upon admission, which was improved to 213 (87.2%) patients on discharge. A total of 115 (47.1%) patients were on ACE‐inhibitor or angiotensin 2 receptor blocker medications on admission and this was improved to 118 (48.3%) upon discharge. A total of 87 (35.6%) patients were on a beta‐blocker, which was improved to 93 (38.1%) patients upon discharge. Conclusion Despite increased implementation of best medical therapy in the community with compliance rates greater than 73% for aspirin and statin therapy, further improvement is warranted. Vascular surgeons should remain vigilant for further opportunities to optimise medical therapy in this high‐risk patient group particularly with antithrombotic, lipid lowering and antihypertensive therapies.